1991
DOI: 10.1093/jn/121.9.1454
|View full text |Cite
|
Sign up to set email alerts
|

High Protein Intake Promotes the Growth of Hepatic Preneoplastic Foci in Fischer #344 Rats: Evidence that Early Remodeled Foci Retain the Potential for Future Growth

Abstract: The effects of successive administration, withdrawal and readministration of high protein diets (20% casein) on the promotional growth, remodeling and regrowth of aflatoxin B1-induced preneoplastic liver lesions (foci) were examined. Weanling male Fischer 344 rats were given 10 intragastric doses of aflatoxin B1 at a level of 250 micrograms/kg body weight over a 2-wk dosing period (initiation). The subsequent 12-wk period was subdivided into four feeding periods, each lasting 3 wk (promotion). Two groups of ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
12
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…However, the 5% casein-fed rats consumed more food throughout the study period than the 20%6 casein-fed rats (about 12-15% by weight) despite the facts that the 5% casein-fed rats were smaller and the diets were isoenergetic as was seen in earlier studies (15,16,37).…”
Section: Resultsmentioning
confidence: 60%
See 1 more Smart Citation
“…However, the 5% casein-fed rats consumed more food throughout the study period than the 20%6 casein-fed rats (about 12-15% by weight) despite the facts that the 5% casein-fed rats were smaller and the diets were isoenergetic as was seen in earlier studies (15,16,37).…”
Section: Resultsmentioning
confidence: 60%
“…Human feeding studies have shown that this level of caloric deprivation is extremely difficult (if not impossible) for most humans to adopt over a lifetime. In contrast, animals fed low protein diets are able to eat more total calories but gain less weight than animals fed high protein diets (15,16). Thus, the starving associated with CR is not similarly associated with PR.…”
Section: Resultsmentioning
confidence: 93%
“…Elevated dietary protein increases(a) MFO enzyme activity by three-to fourfold (29-34); (b) MFOcatalyzed activation of aflatoxin (29) to covalently bind to DNA (35) to cause mutations (36,37); (c) the number and/or size of microscopic clusters (foci) of preneoplastic cells in a dose-dependent manner, although this range of dietary protein begins at about 10% of diet calories that exceeds the recommended allowance (38,39) and ultimately; (d) mature tumors that cause premature death (40)(41)(42). The protein effect size is substantial at each of these disease mechanism stages, appearing within 8 days but even as early as 24 h after administration (43).…”
mentioning
confidence: 99%
“…In the laboratory animal (rat) model, the nutritional (protein) effect remarkably and completely controlled the ability of this very powerful chemical carcinogen to produce tumors, both within the various stages of early neoplasia (reviewed above) and among 2-yr lifetime studies (40)(41)(42). This observation became even more impressive when the protein-induced increase in tumor development was reversed when the dietary protein was decreased (41,44,45).…”
mentioning
confidence: 99%
See 1 more Smart Citation